Instruction level and operating system profiling for energy exposed software. - Sinha, A.
Energy conscious software design can significantly improve the energy efficiency of a portable system. A software energy estimation technique using instruction class profiling is presented. The technique is shown to have an estimation error of less than 3% with trivial runtime overhead, based on a set of application programs evaluated on the StrongARM SA-1100 and Hitachi SH-4 microprocessors. A technique to isolate the switching and leakage energy components of software is outlined. The energy overhead of a real-time operating system is also profiled. The overall impact of system-level software energy management is quantified using the MIT μAMPS system as an application example.
Keywords: Hitachi SH-4 microprocessors; Energy efficiency; Energy exposed software design; Estimation error; Instruction class profiling; Instruction level system; Leakage energy components; Operating system; Portable system; Real-time operating system; Software energy estimation technique; Strong ARM SA-1100 microprocessors; Switching components; System-level software energy management; Trivial runtime; MIT μAMPS system